The impact of training load on the state of the vestibular system of athletes specializing in hand-to-hand combat - Chernozub, A.; Kochina, M.; Kochin, O.; Adamovych, R.; Shtefiuk, I.; Horban, A. (Journal of Physical Education and Sport, 2020)
The purpose of the study was to assess the impact of the training load on the static and dynamic stability of athletes specializing in hand-to-hand combat. The study of static and dynamic stability (SDS) was attended by 20 individuals (the first group) who were not involved in sports professionally, 23 athletes (the second group) engaged in hand-to-hand combat with semi contact with an opponent, and 24 athletes (the third group) specializing in hand-to-hand combat with full contact. The average age of all athletes was (21 ± 1.5) years. Registration of SDS indicators was carried out before and after training, corresponding to the athletes' levels of training, using a stabilographic platform. Statistical analysis of the results of the study was performed using the Statistica 6.0 software package and descriptive statistics methods. The clustering of indicators was carried out according to the k-means algorithm; the reliability of pair differences was assessed using the Wilcoxon and Mann-Whitney criteria. To identify homogeneous groups, SDS indicators were clustered according to the k-means algorithm, which allowed us to distinguish two clusters in each group. We included people with high vestibular functions into the first cluster of each group (55-70% of the athletes), the second cluster (30-45%) encompassed athletes with low vestibular function. In the first cluster of each group, training caused an increase in SDS indicators by 20-25%, except for the equilibrium function quality index (EFQ), which decreased by 9-12%. In athletes with low vestibular functions (the second cluster of each group), the training load led to a significantly larger (36-48%) increase in SDS and a decrease in EFQ by 26-35%. Thus, a significantly more pronounced reaction to the training load was detected in individuals with initially lower vestibular functions.The obtained results showed that elite athletes specializing in hand-to-hand combat may have low SDS. As a result of the training load, vestibular functions were significantly reduced in such athletes. This deteriorated the functional state of athletes and could cause poor performance in competitions. There was no significant dependence of the vestibular functions of athletes on the type of hand-to-hand combat.